Teacher Skills in Teaching Low-Grade Class on Thematic Learning at MI Nurul Islam Pemurus Baru (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The aim of the research is to describe teachers' skills in teaching lower grades in thematic learning at MI Nurul Islam Pemurus Baru. Describe the supporting and inhibiting factors in teaching lower grades in thematic learning at MI Nurul Islam Pemurus Baru. This research method is a type of qualitative research in the form of data description carried out in qualitative descriptive form. The object studied is the teacher's skills in teaching lower grades in thematic learning. The subjects of this research were 10 informants, namely the homeroom teacher of the lower class, the head of the madrasah and 2 students each of the lower class. The results of the research are skills in opening and closing thematic learning, explaining skills in thematic learning, asking questions in thematic learning, skills in providing reinforcement in thematic learning, skills in providing variations in thematic learning, skills in guiding small group discussions in thematic learning, and class management skills on thematic learning. As for supporting factors in teaching, there are several tools, infrastructure and the conditions of some students. Meanwhile, there are several inhibiting factors in teaching, namely the lack of infrastructure and the condition of some of the students. In conclusion, to teach thematics in lower grades, teachers must have special skills that must be mastered so that the learning process can run effectively.